Pemberdayaan Wanita Tani Melalui Pembuatan Pestisida Nabati di Padukuhan Dabag, Kalurahan Condongcatur, Kabupaten Sleman - Sandika Cahya Haq; Siti Nurlaela; R. Hermawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to enhance the capacity of the Women Farmers Group (KWT) in implementing environmentally friendly agriculture through training in the production of botanical pesticides. The methods used included counseling, hands-on practice, and evaluation through a participatory approach. The evaluation was based on the Kirkpatrick model at the reaction and learning levels. The results showed significant improvements in knowledge (from 53% to 93%), attitude (from 76% to 97%), and skills (from 0% to 97%). Participants also expressed high satisfaction with the training activities, with an average response score of 4.56. This program successfully promoted behavior change and raised awareness of sustainable and safe agricultural practices.